Predator–Prey Movement Interactions: Jaguars and Peccaries in the Spotlight - Alegre, Vanesa Bejarano [UNESP]; de Faria Oshima, Júlia Emi [UNESP]; Kanda, Claudia Zukeran [UNESP]; Jorge, Maria Luisa S. P.; Keuroghlian, Alexine; Morato, Ronaldo G.; Ribeiro, Milton Cezar [UNESP]; Börger, Luca (Wiley, 2025)
Understanding how landscape structure influences predator–prey dynamics is critical for conservation. This study analyzed jaguar-peccary interactions, revealing uncommon close distances and prevalent 3–5 km ranges, especially away from grasslands. Low peccary densities increased interactions. Findings inform conservation strategies, highlighting landscape structure and prey density roles in maintaining Pantanal's balance.
Keywords: carnivores; conservation; forest-edge dynamics; landscape structure; Pantanal; Panthera onca; spatial–temporal dynamics; Tayassu pecari; ungulates